Perceived flood risk and insurance status among Pahang residents: A comparative study - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Ju, Soon Yew; Noor Amira Syazwani, Abd Rahman (Penerbit UMPSA, 2024)
Flooding has been a regular concern in Pahang, Malaysia, causing significant property damage and disrupting lives. Relying largely on the government to provide financial help in the event of floods may not be a sustainable approach, given the government’s current financial strain. It is crucial for Pahang residents to proactively uptake flood insurance to ensure their resilience in the face of flood-related disasters. Understanding residents’ perceptions of flood risk and their insurance status is crucial for effective disaster management and the development of mitigation strategies. The study intends to investigate the differences in perceived flood risk levels among residents with different insurance statuses. The study employed a quantitative approach, involving a sample of 116 respondents residing in Pahang. The results of the independent t-test reveal significant differences in perceived flood risk (perceived susceptibility and perceived severity of floods) between insured individuals and uninsured individuals. This study will make a valuable contribution to the existing body of knowledge on flood risk and flood insurance within the Malaysian context, with a specific focus on the state of Pahang. The results will contribute to the development of targeted interventions, public awareness campaigns, and policy recommendations aimed at improving flood resilience and encouraging greater insurance uptake among Pahang residents.